2003
DOI: 10.1029/2002gl015898
|View full text |Cite
|
Sign up to set email alerts
|

The salinity normalization of marine inorganic carbon chemistry data

Abstract: Normalization to a constant salinity (S) is widely used for the adjustment of marine inorganic carbon chemistry data such as total alkalinity (AT) and total dissolved inorganic carbon (CT). This procedure traces back to the earliest studies in marine chemistry, but ignores the influence of riverine input of alkalinity and of dissolution of biogenic carbonates in the ocean. We tested different adjustment possibilities for AT and conclude that in most parts of the surface ocean the normalization concept does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
222
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(239 citation statements)
references
References 20 publications
3
222
1
Order By: Relevance
“…This expression takes into account the effects of organic matter remineralization on A T (Fraga and Álvarez-Salgado 2005). The cycling of carbonate minerals is the major biogeochemical process affecting seawater alkalinity (Friis et al, 2003), which is the reason why ∆CaCO 3 can be expressed as a function of A T . In fact, alkalinity was historically explained as "being a measure of its potential carbonate of lime" (Dittmar, 1884).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…This expression takes into account the effects of organic matter remineralization on A T (Fraga and Álvarez-Salgado 2005). The cycling of carbonate minerals is the major biogeochemical process affecting seawater alkalinity (Friis et al, 2003), which is the reason why ∆CaCO 3 can be expressed as a function of A T . In fact, alkalinity was historically explained as "being a measure of its potential carbonate of lime" (Dittmar, 1884).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The normalization to a common S=35 removes the A T -S co-variation, compensates for freshwater balance effects and brings all surface waters close to subsurface conditions. Although this normalization scheme ("zero alkalinity at zero salinity") comes with certain caveats (Friis et al, 2003), the errors arising from its use are not large when intended for back-calculating C ant , because it would affect equally industrial and preindustrial values. Moreover, the recommendations of alternative alkalinity normalizations in the work from Friis et al (2003) refer to surface (upper 50 meter) rather than subsurface waters.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore used r N/P = 16. In order to avoid the change of water mass in the isopycnal grid analysis, we also addressed all the data by normalizing them to salinity of 35 using the optimal salinity-normalization scheme with a non-zero freshwater endmember (Friss et al 2003), which were shown with the prefix 'n'. As a non-zero freshwater endmember, we here assumed Alk = 589 mmol kg -1 , DIC = 294 mmol kg -1 , AOU = 0 mmol kg -1 and N* = 0 mmol kg -1 based on the climatological riverine data (Andreev and Pavlova 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Using the method developed by Friis et al (2003), DIC is normalized to salinity to remove the overlying salinity signal to better determine biological and anthropogenic impacts. …”
Section: Computational Analysismentioning
confidence: 99%